Peningkatan Kemampuan Guru dalam Membuat RPP Tematik Melalui Workshop dengan Variasi Model Jig Saw - Dewi Muninggar (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2019)
The 2013 curriculum that has been re-enacted by the government, must be accompanied by an increase educators quality. Actually there are several problems faced in the implementation of this curriculum, including teachers do not yet know the form of RPP specifically in the thematic, scientific approach to the 2013 curriculum. This study uses a school action research design (PTS). In each cycle includes planning, implementing actions, observing, and reflecting. In the first cycle, it was known that the teacher's ability to make high-class thematic RPPs was only 3 teachers out of 7 or 42.86%. Furthermore, the implementation of the second cycle shows an increase in the ability to make thematic lesson plans for teachers. This is evidenced that there are 6 out of 7 teachers based on the results of the assignment obtained the ability to make high thematic thematic RPPs. The percentage of high category teachers is 85.71%. This shows that workshops on variations in jigsaw models can improve the ability of teachers to make thematic lesson plans for learning. Teachers and teachers should continue to improve their competence in making lesson plans, while principals try to continue to facilitate their supporting facilities.